Chiral topologies for composite morphing structures – Part I: Development of a chiral rib for deformable airfoils. Issue 7 (26th June 2015) - Airoldi, Alessandro; Bettini, Paolo; Panichelli, Paolo; Oktem, Mehmet F.; Sala, Giuseppe
<x xml:space="preserve">Abstract</x> The paper moves from a technological process developed in previous works to produce chiral honeycombs made of thin composite laminates. Such approach is applied in this work to manufacture the morphing ribs for a variable camber wing‐box. The specifications for such components are obtained by developing a finite element model of a demonstrator, which is designed taking into account aeroelastic performances, structural, and technological issues. In the first part of the paper, the design of such a demonstrator is presented and the role of composite chiral ribs with auxetic behavior is outlined. Production, testing, and numerical studies of manufacturing trials are performed to assess the technological process applied to small‐sized chiral units made of different materials, to investigate their mechanical properties, and to validate a numerical approach for design and analysis. A complete chiral composite rib is then produced and tests are carried out to verify the overall structural response and to validate the numerical approach.